1994
DOI: 10.1177/095632029400500608
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Metabolism of 3′-azido-3′-deoxythymidine and 2′,3′-dideoxyinosine in Combination in the Absence and Presence of Ribavirin

Abstract: SummaryWe examined the intracellular ph9sphorylation of 3'-azido-3'-deoxythymidine (AZT)Jhd 2',3'-dideoxyinosine (ddl) and the effects on rNTP and dNTP pools when AZT and ddl were incubated separately and in combination in lymphocytes. We also compared the effect of adding ribavirin (RBV) to the two-drug combination of AZT + ddl.AZT and ddl, used singly or in combination, had no effect on the dNTP pools of CEM Iymphoblastoid cells. Neither did the combination of AZT + ddl have any effect on the rNTP pools. RBV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
10
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 36 publications
2
10
0
Order By: Relevance
“…Mechanisms focusing on alterations in dNTP pools or alterations in the amount of AZT triphosphate formed seem unlikely, given that Palmer and Cox (26) found that the level of AZT phosphorylation was unchanged regardless of whether human lymphoblastoid cells were incubated with AZT alone or in combination with ddI. Instead, they observed a modest increase in the level of ddI-triphosphate following AZT-ddI coexposure of these cells.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms focusing on alterations in dNTP pools or alterations in the amount of AZT triphosphate formed seem unlikely, given that Palmer and Cox (26) found that the level of AZT phosphorylation was unchanged regardless of whether human lymphoblastoid cells were incubated with AZT alone or in combination with ddI. Instead, they observed a modest increase in the level of ddI-triphosphate following AZT-ddI coexposure of these cells.…”
Section: Discussionmentioning
confidence: 99%
“…Cell cellular dNTP pools, in agreement with recent observations (Gao et el., 1993;Palmer and Cox, 1994b;Palmer and Cox, 1995). AZT was phosphorylated to a much lower extent in uninfected fibroblasts than in lymphocytes, but the amount of AZT TP formed represented a greater percent of the total AZT metabolites.…”
Section: Drugsmentioning
confidence: 99%
“…However, ribavirin and doxorubicin significantly reduced ZDV phosphorylation in all cells. Ribavirin has been shown previously to antagonize the phosphorylation of pyrimidine dideoxynucleosides (2), and the mechanism is thought to involve a ribavirin-induced increase in nucleoside TP levels leading to feedback inhibition of thymidine kinase (29) and hence conversion of ZDV to ZDV-MP (20). As doxorubicin exerts its pharmacological effect by insertion between DNA base pairs, it is not clear how it alters ZDV phosphorylation.…”
mentioning
confidence: 95%